Impact of community-based rehabilitation on attainment of sustainable development goals: The case of selected districts in Zimbabwe - Pasara, Michael Takudzwa (Frontiers in Communication, 2022)
Several factors including droughts, cyclones, COVID-19, and inconsistent economic policies contributed to the challenges faced by children and persons with disabilities (PwDs) in rural areas of Zimbabwe. Consequently, there was a higher risk of low quality of life, poverty, and limited access to basic services such as education and healthcare. Various community-based rehabilitation (CBR) programs were implemented to address the violation of rights and access to services and participation by PwDs in general. This study used a mixed method approach to analyze the impact of CBR programs taking into account the five themes of the United Nations Convention of Rights of Persons with Disabilities (UN-CRPD): education, health, livelihoods, social protection, and participation. Respondents included core beneficiaries, caregivers, teachers, community health workers, and other key stakeholders. Results indicated that 61% were female respondents and 39% were males. Approximately 84% of rural families survive on less than USD 20.00 per month with the modal household having 5 to 9 members per household. Approximately 81% have received at least secondary education although some did not complete Ordinary Level mostly due to lack of funding for registration fees at the time of writing. However, none had tertiary education. The reach of CBR was as high as 92% of respondents received training on disability management; 71% on income generating projects (IGPs) and 84% on Internal Savings and Lending (ISAL) although only 32% received funding. The study recommends funding for self-help groups, increased technical support, functional disability-friendly toilets, and orthopedic centers, scaling up of programs at a national level and adoption by the relevant agencies, decentralization by government officials to reduce red tape and accelerate programs, and training of trainers for additional capacity building. Improved latitude for NGOs and consistent economic policies are also needed to sustain IGPs.